Institutional Research Ethics Committees that have Evaluated Clinical Trials contemplated in the Peruvian Regulations 2010-2023 - Rojas-Quiche, Katherine Milagros (2025)
Introduction: The Declaration of Helsinki recognizes the importance of Institutional Research Ethics Committees (IREC) in experimental studies for consideration, comments and guidance; which has been included in international and Peruvian legislation as a standard of good clinical practice. This study seeks to characterize the IREC that have evaluated clinical trials (CT) framed in the Peruvian Regulation, period 2010-2023. Material and methods: Secondary source. The population was the CT submitted to the National Institute of Health. Inclusion criteria: CT registered in the Peruvian Registry of Clinical Trials, and as exclusion criteria: i) CT with repeated registration, ii) registry without information on the IREC. A descriptive analysis was performed. Results: 927 CT were analyzed, which were evaluated by 36 IREC. The three IREC with the highest number of CT evaluated were private. The private IREC had as their main users private clinics that did not have IREC. Conclusion: There were 36 IREC that evaluated CT in the period 2010-2023. The three IREC that have evaluated the most CT are private. Private IREC do not usually have the research institutions to which they belong as users.